Optimization of HPLC Measurements Using Addictive Drug Leflunomide and its Validation Studies under Different Medium: Exploring the Effects of Leflunomide on Rheumatoid and Psoriatic Arthritis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Leflunomide is an immunomodulatory drug inhibiting dihydroorotate dehydrogenase an enzyme involved in de novo pyrimidine synthesis. Genuine anti proliferative activity has been proven. Additionally, the several experimental models (both in vivo and in vitro) have demonstrated an anti-inflammatory effect. This double action is supposed to slow progression of the disease and to cause remission or relief of symptoms of rheumatoid arthritis and psoriatic arthritis such as joint tenderness and decreased joint and general mobility in human patients.